Association between sleep duration and blood pressure in adolescents - Paciencia, I (2013)
In adults, sleep has an important role in the development of cardiovascular diseases. However, in young adolescents, the effect is unclear. The purpose of this cross-sectional study was to evaluate the association between sleep duration and blood pressure (BP) in subjects of 13 years of age. We evaluated 1771 adolescents as part of a population-based cohort (Epidemiological Health Investigation of Teenagers). Sleep duration was estimated based on the difference between self-reported usual bedtimes and wake-up times, and adolescents were classified into three categories: 8.5 h (reference class), >8.5 h and <9.5 h, and 9.5 h. BP was measured using the auscultatory method and was classified as high if the systolic or diastolic BP was 90th percentile according to the American Academy of Pediatrics. To evaluate the association between BP and sleep duration, the odds ratios (ORs) and 95% confidence intervals (95% CIs) were computed by fitting binary logistic regression models with adjustments for caffeine intake and depressive symptoms in females and for caffeine intake and sports activities in males. The mean (s.d.) sleep duration was 9.0 (0.80) h per day. The prevalence of high BP was 32.5%, higher in males (35.3%) than in females (30.1%, P=0.019). After adjustment, in females, a positive association was found between sleep duration and high BP (>8.5 and <9.5 h: OR=1.56, 95% CI 1.07–2.27; 9.5 h: OR=1.83, 95% CI 1.23–2.70). Among males, no significant association was found between sleep duration and BP. Sleep duration was positively associated with BP in both sexes, although after adjustment for potential confounders, this association was significant only for female adolescents.